Intersections of religion and climate-related security risks: Insights from a systematic review - Tarusarira, Joram; Scartozzi, Cesare Marco; Elnur, Rawie Ibrahim (Brill, 2024)
This study explored the significance of religion in the climate security discussion. Despite being extensively explored in conflict studies, the role of religion in climate security discourse is still largely overlooked. This is surprising, given that it significantly impacts decision-making during crises. The intersection of climate change and religious beliefs and diversity exacerbates conflicts across Africa. Recent studies have highlighted the pivotal role of religion in shaping responses to climate-induced security risks, yet it is often sidelined in climate security discourse. Through a systematic literature review, this study identifies gaps and proposes future research directions. The findings underscore the peripheral role of religion in climate security literature and the lack of interdisciplinary coherence. By recognizing the multifaceted role of religion in crises, this study aims to provide crucial insights into the complex dynamics of the religion-climate-climate security nexus.